Study of Fishers' Perceptions on Environmentally Friendly Fishing Gear Criteria on The East Coast of North Sumatra - Brewon, Marianus O.; Wiyono, Eko Sri; Sudarmo, Agnes Puspitasari (Torani Journal of Fisheries and Marine Science, 2022)
This study aimed to describe the development of types of fishing gear in the waters of the east coast of Sumatra from Belawan Waters to Serdang Bedagai Waters and to examine the perceptions of fishers based on the social characteristics of fishers towards environmentally friendly fishing gear based on the Code of Conduct for Responsible Fisheries (CCRF). The method used in this research is descriptive research using the survey method. The population in this study were fishers based in Belawan and Serdang Bedagai waters and using traps and gill nets, as many as 6943 people, with the simple sampling method or slovin method, the results of the sample count were 100 people from the population. Based on eight categories (CCRF) to understand fishers' perceptions of environmentally friendly fishing gear, including the level of selectivity, biodiversity, ecological diversity, not destroying habitat, the safety of fishers and consumers, based on social conditions, based on biodiversity, and based on fish quality, the level of very understanding is 13.2 %, understand 25.2%, neutral 26.7%, don't understand 23.3% and don't understand 11.4%. This study results indicate that the respondents, in general, have begun to realize environmentally friendly fishing gear based on the CCRF.